2023
DOI: 10.1002/berj.3851
|View full text |Cite
|
Sign up to set email alerts
|

Satisfied teachers are good teachers: The association between teacher job satisfaction and instructional quality

Abstract: Instructional quality is associated with better academic outcomes for students. This study aimed to investigate how teachers' job satisfaction was associated with clarity of instruction and cognitive activation as measures of instructional quality. In addition, we investigated whether this association between teachers' job satisfaction and instructional quality was mediated by teacher–student relationships. Drawing on the 2018 Teaching and Learning International Survey (TALIS), we compared participants from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 114 publications
(147 reference statements)
0
13
0
1
Order By: Relevance
“…Therefore, they concluded that teachers appear to adjust their teaching methods based on the needs of their students. A more recent study of teachers from Eastern and Western worlds reports a positive relationship between teachers' job satisfaction and instructional quality and, furthermore, how this relationship is partially mediated by better student‐teacher relationships (Harrison et al., 2023). Even though many studies using TALIS data looked at the overall quality of instruction by combining different aspects into one model, some researchers also separately explored the three specific dimensions of instructional quality.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they concluded that teachers appear to adjust their teaching methods based on the needs of their students. A more recent study of teachers from Eastern and Western worlds reports a positive relationship between teachers' job satisfaction and instructional quality and, furthermore, how this relationship is partially mediated by better student‐teacher relationships (Harrison et al., 2023). Even though many studies using TALIS data looked at the overall quality of instruction by combining different aspects into one model, some researchers also separately explored the three specific dimensions of instructional quality.…”
Section: Resultsmentioning
confidence: 99%
“…As part of a larger project, which aimed to enhance STEM teachers’ well-being and facilitate their professional development [ 14 ], our research goal was to examine the relationships among novice STEM teachers’ PTs, PSS, WE, and JS. Thus, a quantitative cross-sectional survey was the most efficient and appropriate method [ 55 ], as it can help collect data regarding these variables in a relatively short period of time [ 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, to address this issue, it is very necessary to explore what factors influence STEM teachers’ JS. Furthermore, studies have revealed the significance of STEM teachers’ JS in the process of improving the quality of STEM education [ 14 ] and students’ STEM learning outcomes [ 15 ]. This also highlights the importance of increasing STEM teachers’ JS.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, this collection of papers contains no independent research conducted with teacher samples from South America or Africa, and only a few studies have been conducted in Asia or Australia. However, such research is essential to improving our understanding of the impact of cultural differences on the outcomes of teacher wellbeing, a need that was highlighted by Harrison et al (2023).…”
Section: Directions Of Future Researchmentioning
confidence: 99%